Effect of the thermal treatment on the magnetic and structural properties of cobalt ferrite particles. Issue 14 (1st November 2016) - Venturini, J.; Piva, D.H.; da Cunha, J.B.M.; Bergmann, C.P.
Abstract: We herein report a study on the sol-gel synthesis of CoFe2 O4 and the effect of thermal treatment on the product outcome. Xerogels treated at 750, 800 and 850 °C had their structural and magnetic properties thoroughly studied, in order to correlate their synthesis conditions to the positions in which the cations are inserted in the spinel structure. X-ray diffractograms exhibit reflections representative of the spinel structure and demonstrate that the thermal treatment does not affect the lattice parameters of the material. Mossbauer spectroscopy studies indicate a very low inversion degree in the synthesized spinels, which is very unusual for CoFe2 O4 . A maximum in coercivity of 1405.2 Oersted was achieved for the sample treated at 800 °C.